2013
DOI: 10.5937/ekonhor1303197v
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of indicators of regional competitiveness: The case of the Republic of Serbia

Abstract: The identification and analysis of the indicators of regional competitiveness is the most important phase of the process of measuring competitiveness. However, prior to the measurements, it is necessary to determine whether there is a high correlation between the selected indicators or not. The aim of this paper is to determine whether there is a high correlation between the most important indicators of regional competitiveness or not. The subject of this paper are the indicators of competitiveness in Serbia's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…In order to correctly identify the connection and dependence among these factors as well as among the 12 pillars of competitiveness, the authors suggest, for further research, the use of a complex method of correlation analysis by which the correlation value would be determined by a correlation coefficient, the value of which would range from -1 to +1 (Figure 2). According to Vukovi (2013), this method has confirmed that there is interdependence between certain indicators and regional competitiveness factors, especially in investments in science, technology and innovation and in improving the business environment, which is directly related to increasing competitiveness. [7] It is important to point out that the authors are cautious when it comes to the guidelines for increasing competitiveness only by individual pillars because it is precisely due to their interdependence the question arises as to whether a country's competitive index can grow in continuity in this way?…”
Section: Guidelines For Increasing the Competitiveness Of Bih Economymentioning
confidence: 97%
See 1 more Smart Citation
“…In order to correctly identify the connection and dependence among these factors as well as among the 12 pillars of competitiveness, the authors suggest, for further research, the use of a complex method of correlation analysis by which the correlation value would be determined by a correlation coefficient, the value of which would range from -1 to +1 (Figure 2). According to Vukovi (2013), this method has confirmed that there is interdependence between certain indicators and regional competitiveness factors, especially in investments in science, technology and innovation and in improving the business environment, which is directly related to increasing competitiveness. [7] It is important to point out that the authors are cautious when it comes to the guidelines for increasing competitiveness only by individual pillars because it is precisely due to their interdependence the question arises as to whether a country's competitive index can grow in continuity in this way?…”
Section: Guidelines For Increasing the Competitiveness Of Bih Economymentioning
confidence: 97%
“…According to Vukovi (2013), this method has confirmed that there is interdependence between certain indicators and regional competitiveness factors, especially in investments in science, technology and innovation and in improving the business environment, which is directly related to increasing competitiveness. [7] It is important to point out that the authors are cautious when it comes to the guidelines for increasing competitiveness only by individual pillars because it is precisely due to their interdependence the question arises as to whether a country's competitive index can grow in continuity in this way?…”
Section: Guidelines For Increasing the Competitiveness Of Bih Economymentioning
confidence: 97%
“…Regional competitiveness literature in academic and popular press, includes three thematic areas: (1) definitions and conceptualizations ways for competitiveness measuring; (2) benefits and shortcomings of strategies for increasing competitiveness;…”
Section: Introductionmentioning
confidence: 99%
“…If the strategy applied to regional competitiveness is not effective and if factors of competitiveness are used not optimally, then the regions will lose its competitive position, which will lead to a negative impact on national competitiveness (1). Many authors, including Krugman (2,3), assumed that competitiveness refers to achieve higher productivity, measuring the value of goods and services per unit factor production of a single territory, which will affect growth and standards of living.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Sala-I-Martin created Global Competitiveness Index (GCI), which envelops macroeconomic and microeconomic competitiveness factors (Sala-i-Martin, X., et al, 2008). At the micro level, competitiveness is the ability of companies to compete, grow and be profitable (Martin, n.d.), or the ability of a company to produce and sell products and services at a lower price compared to its competitors (Vukovic, 2013). Competitiveness at the macroeconomic level is associated with strenthening productivity at the national level leading to rising living standards, expanding employment opportunities, and the ability of a nation to maintain its international obligations (Martin, n.d.).…”
Section: Introductionmentioning
confidence: 99%